Reliability of methods to determine arterial oxygen-haemoglobin saturation in immobilized southern white rhinoceros (Ceratotherium simum simum) - Meyer, Leith Carl Rodney (University of Pretoria, 2023)
Thesis (PhD)--University of Pretoria, 2022.